(untitled) (Indian Journal of Arid Horticulture, 2025)
In the present investigation the response of 6, 8 and 10 week old seedlings of onion cv. N-53 was studied along with foliar application of Cycocel (500 & 1000ppm), Ethephon (2000 & 2500ppm) and Paclobutrazol (1000 & 2000ppm) in factorial RBD replicated thrice during Rabi season of 2014-2015 at Division of Vegetable Science and Floriculture, SKUAST, Jammu. The results showed maximum equatorial diameter of bulbs (6.11cm) and TSS (9.63°B) in 8 week old seedlings. Minimum bolting was recorded in 8 week old seedlings (16.99%) which was statistically superior to 10 and 6 week old seedlings. Significantly higher days to first bolt was observed in 8 week old seedlings (99.71 days) over 10 and 6 week old seedlings (96.19 and 77.76 days), respectively. It is evident from the results; application of Paclobutrazol 2000ppm recorded the maximum equatorial diameter of bulbs (5.79cm) and TSS (9.49°B) along with lowest bolting (35.99%) up to 97.22 days after transplanting. Interactive results between seedling age and plant hormones showed maximum equatorial diameter of bulbs (6.80cm), TSS (11.50°B) and lowest bolting (9.64%) in the treatment having 8 week old seedlings with Paclobutrazol 2000 ppm (A,P,). Seedlings of 8 week old attained A (5.70%) and A grade (15.00%) bulbs recovered along with other marketable grades like B (45.00%) and C (28.00%). While the seedlings aged 6 and 10 week old could not attain bulbs of A and A grade bulbs. The storage studies also pointed out minimum rotting (72.20%) and total weight loss (70.00%) in this treatment.